Design And Implementation Of Web-Based E-Learning At Smk Negeri 1 Tondano - Liando, Olivie E. S; Muyu, Ronaldo; Mewengkang, Alfrina; Kembuan, Djubir R.E (International Journal of Information Technology and Education, 2022)
In the midst of the current COVID-19 pandemic, the utilization of online learning support facilities has not been optimal because there is no e-learning application at SMK Negeri 1 Tondano. Based on the existing conditions, the learning process through e-learning technology with an internet connection allows learning to be carried out more easily. This study aims to design and implement web-based e-learning at SMK Negeri 1 Tondano. The research method used is Scrum which is one of the derivative development methods of Agile Development. The results of this study indicate that the existence of e-learning applications can make it easier for teachers to provide materials and assignments and students can easily access learning materials and do assignments/exams given by the teacher. Using the Scrum method can make it easier to create applications.